2006
DOI: 10.1080/10473289.2006.10464433
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and Biological Mechanisms of Nitric Oxide Removal from Waste Air in Biotrickling Filters

Abstract: Nitric oxide (NO) may participate in the ozone layer depletion and forming of nitric acid. Abiotic and biological mechanisms of NO removal from waste gases were studied in a biotrickling filter. The abiotic NO removal rate in the biotrickling filter was estimated by a review of the literature. The abiotic and biological removals were also verified in the biotrickling filter. The result has shown that chemical oxidation and bionitrification were both involved in the NO removal. It was found that the NO removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The chemical absorption of NO and biological regeneration of Fe(II)EDTA taking place in the same reactor may have the advantages of easy operation and economical cost. Thus, a biofilter was chosen for NO removal in this study due to high porosity, high nutrient availability, high moisture retention capacity, and high buffering capacity to sustain microbial growth on a suitable support matrix .…”
Section: Introductionmentioning
confidence: 99%
“…The chemical absorption of NO and biological regeneration of Fe(II)EDTA taking place in the same reactor may have the advantages of easy operation and economical cost. Thus, a biofilter was chosen for NO removal in this study due to high porosity, high nutrient availability, high moisture retention capacity, and high buffering capacity to sustain microbial growth on a suitable support matrix .…”
Section: Introductionmentioning
confidence: 99%
“…The abiotic and biological removals were also verified in the BTF and it was found that chemical oxidation and bionitrification were both involved in the NO removal (Chen and Ma, 2006;Chou and Lin, 2000). In the case of the flue gas containing NO, O 2 concentration was often around 3-8%, thus only chemical and biological reactions under 8% were conducted and compared at different temperature (25 and 50 C).…”
Section: Effect Of Oxygen On No Removalmentioning
confidence: 99%
“…BTFs contain inert packing materials (such as ceramics, compost) that provide sufficient surface area for gas/liquid mass transfer and biofilm growth. Several studies have proven the possibility of NO x removal in biofilters and BTFs at mesophilic temperatures (Chen and Ma, 2006;Jiang et al, 2009;Jun et al, 2008;Yang et al, 2007). However, in coal-fired power plants, influent flue gas stream for a NO x removal reactor is the emissions from a sulfur dioxide scrubber, which employs water/limestone slurry to absorb sulfur dioxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated that bioreactors can be successfully employed for the removal of NO x from combustion gases in a laboratory, but the high Henry’s constant of NO restricts a higher efficiency of NO removal . It was confirmed through abiotic and biological removals in the biotrickling filter that NO removals in high concentration (1000 ppm or higher) were in large measure the result of abiotic removal in both gas-phase and liquid-phase reactions while bionitrification was the main process of NO removal in low concentration (less than 100 ppm) . Hence a promising technique called chemical absorption-biological reduction (CABR) integrated approach has been developed recently for the NO x removal from flue gases. In this approach, Fe(II)EDTA is used to overcome the limitation of biological treatment processes by promoting the NO absorption into scrubber liquor.…”
Section: Introductionmentioning
confidence: 99%